Direct and indirect healthcare costs of ocular diseases in Italy: a literature review on glaucoma, diabetic retinopathy, and macular degeneration - Pennisi, Flavia; Gentile, Leandro; Borlini, Stefania; Gianfredi, Vincenza; Signorelli, Carlo (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Glaucoma, diabetic retinopathy, and age-related macular degeneration impose substantial economic burdens on healthcare systems due to their high prevalence and chronic nature. Nevertheless, comprehensive Italian data is limited. This study aims to collect Italian evidence on the economic impact of these conditions to support more effective healthcare planning. Study Design. Systematic review. Methods. A systematic literature search was conducted in accordance with PRISMA guidelines across PubMed, Scopus, Web of Science, and EMBASE databases. Studies reporting cost evaluations of managing glaucoma, diabetic retinopathy, and age-related macular degeneration in Italy were included. Direct, indirect and non-medical costs were considered. Results. The review included 23 studies exhibiting considerable heterogeneity in timeframes, regions, and economic evaluation approaches. For glaucoma, annual direct costs ranged from €788.70 for early-stage cases to €8,368.51 for advanced cases requiring surgery. Annual costs associated with diabetic retinopathy ranged from €4,050 to €5,799 per patient, depending on disease severity and treatment approach. The financial burden of age-related macular degeneration varied considerably, with costs ranging from €1,399.20 for early-stage cases to €3,973.30 for advanced stages. Although non-medical and indirect costs, such as lost productivity and caregiving expenses were less frequently assessed, they represented a significant contributor to the overall financial burden. Conclusions. This study highlights the substantial economic burden ocular diseases place on the Italian healthcare system. Early intervention and preventive strategies could reduce the long-term costs of managing diabetic retinopathy and age-related macular degeneration. Further research into indirect costs and cost-effective interventions is necessary to support more efficient healthcare resource allocation.